is supposed to be a function such that
![f^(-1)(f(x))=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/efzoubmdl2afeglyyw0qq6xup3pmx09gnu.png)
In this case, we need
![f^(-1)(\sqrt[3]{x-2})=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7jiatx7crl2nht586fet04xqqykeemg5vp.png)
To recover
from
, we would first need to raise
to the third power:
![(\sqrt[3]{x-2})^3=x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dpga120o0ff5w6pim6kb5w53ke93nwoj7r.png)
Then add 2:
![(x-2)+2=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g3zl36zu0z0k2y2buoc0f3lm583orvcoxr.png)
To recap, we carried out
![f^(-1)(\sqrt[3]{x-2})=(\sqrt[3]{x-2})^3+2=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ctm472p7p59kfgukefuv3hhj32osrr393b.png)
which implies that the inverse function is
![f^(-1)(x)=x^3+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cj095e7eruqwxw5fvw7yoh0srvtzzwc20o.png)
To verify: we should also have that
. We get
![f(x^3+2)=\sqrt[3]{(x^3+2)-2}=\sqrt[3]{x^3}=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9jyxnx9dip9oz1c5mqcqik8kxirkazwupn.png)